A comparison between the ocean and offshore photovoltaic production system into microgrids: benefits and limits - Saad Chayma; Flah Aymen; Flah Aymen; Flah Aymen; Flah Aymen; Abdulaziz Alkuhayli; Rahmat Ullah; Claude Ziad El-Bayeh (Frontiers in Energy Research)
The current work offers a detailed comparison of the advantages and disadvantages of microgrids concerning the developments of photovoltaic (PV) production installed near the shore and those installed offshore. As demand for renewable energy increases, integrating offshore and marine photovoltaic systems offers a promising approach to increase energy production while minimizing land use. This study explores the inherent advantages of offshore photovoltaic systems, including higher energy production due to the cooling effect of water, reduced reliance on land, and the ability to tap into sustained marine solar resources. On the other hand, this paper also addresses challenges associated with these systems, such as: B. Increased installation complexity, vulnerability to harsh ocean conditions, and potential impacts on marine ecosystems. The results in this paper show good performance for both offshore and floating PV systems, except that the offshore PV system excels over the other system by 3.13% in energy production. Moreover, the difference in the annual efficiency of the two PV systems reached 0.55%. These values are considered low because both systems are installed in water, given that both systems benefit from lower temperature and solar irradiation values. Nevertheless, these two systems equally present their own unique challenges including, but not limited to, operational and maintenance cost increase, effect on marine ecology and the technical hindrances on installation and grid interconnectivity. The aim of this review is to disentangle the achievements made regarding the current state of the art in floating photovoltaic technologies. When dealing with performance metrics, two solutions are examined in order to demonstrate the feasibility of providing the energy needs in an ecological way.